Stock prices and dynamics of aggregate investment: evidence from Malaysia - Ibrahim, Mansor (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The paper analyzes empirically the role of stock prices in the aggregate investment function for an emerging market, Malaysia. The neoclassical investment theory that relates investment to output and lending rate and augmented with stock prices is used as an empirical basis. Applying a series of time series techniques, we document evidence suggesting favorable effects of stock market increases on aggregate investment especially in the long run. Likewise, the stock market seems to anticipate future variations in output. Reasonably, as suggested by our empirical results using vector error correction modeling, variance decompositions and impulse response functions, the aggregate investment tends to respond faster and with larger magnitude to stock price shocks than real output does. Having noted these, our analysis does not rule out adverse short run real effects of cyclical variations in stock prices.